Biological tools in the diagnosis of lung cancer. - Robin Ghosal (2010)
SummaryLung cancer is the most common cancer worldwide with 1.3 million new cases diagnosed each year. The 5-year survival rate is much lower than other common cancers such as breast and prostate cancer. Several large-scale screening programmes using existing technologies over the past 40 years have not yet reduced mortality rates from lung cancer. We have studied new technologies on sputum and exhaled breath to assess their potential for diagnosis. Reliable, non-invasive and cheap diagnostic tests are the cornerstone for any future screening programme. The first study tests the sputa of patients with suspected lung cancer and healthy controls with Fourier Transform Infra-Red (FTIR) spectroscopy. We developed a predictive model based on two wavenumbers, to differentiate those with proven lung cancer versus healthy controls with a sensitivity of 93% and specificity of 91%. When we included the sputa of patients having tests for lung cancer initially but with no evidence of cancer after one year (“high-risk” group), this only partially reduced the model’s predictive ability. The second study assessed the sputa from the same cohorts with a panel of gene antibodies (p16, p53, p63, EGFR and cyclin D1). Results were not discriminatory with low sensitivity (8-42%), suggesting immunohistochemistry on sputa cells will not be a useful diagnostic tool. Our final study assessed exhaled volatile organic compounds (VOCs) in \the breath of newly diagnosed lung cancer patients and in healthy controlsj using gas chromatography - mass spectrometry. 29 cancer-exclusive VOCswere identified and 25 further VOCs were universally higher in the cancer cohort, allowing correct classification of 89% of cancer patients. We conclude that two of the three novel techniques (sputum FTIR and exhaled VOCs) could successfully distinguish cancer from healthy control subjects and show potential as screening modalities in further larger scale studies.